Intellectual property and its protection at Innovation And Commercialization Centre (ICC), UTM - Noor Izzatie Ngosman, 1996-, author; Aslan Amat Senin, supervisor; Sekolah Perniagaan Antarabangsa Azman Hashim (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2020)
Project Paper (Sarjana Muda Pengurusan (Pemasaran)) - Universiti Teknologi Malaysia, 2020